The Public Service Management of the Medan City Government in Combating Illegal Charges (International Journal of Cultural and Social Science, 2023)
The practice of illegal levies in the implementation of public services is an act that is very detrimental to various parties, in this case the community and the state are victims. The practice of illegal fees can be prevented by improving the quality of service management based on 3 main principles, namely transparent, accountable, and participatory. This paper will review the efforts of the Medan City Government in eradicating the practice of illegal levies (Pungli) in Medan City. This research is a qualitative research with a descriptive approach to literature study. The data is obtained by taking a public assessment of the quality of service in the public sector in the review column or comments contained in the media or aspiration channels within the Medan City Government including websites, social media channels, and so on. Data analysis was carried out by data reduction, data presentation and drawing conclusions. The results showed that there was a decrease in the number of illegal levies in the public sector of the Medan City Government